Evaluation of scientific research and development works providing diversification of production - A. M. Batkovskiy; M. A. Batkovskiy; Е. Iu. Khrustalev (Russian Journal of Economics and Law)
Objective: to develop methodological foundations and tools for evaluating research and development activities carried out in order to diversify production at enterprises of the military-industrial complex, as well as to predict their prices. Methods: comparative analysis, economic and mathematical modeling, and expert assessments.Results: the implementation of diversification measures carried out by enterprises of the military-industrial complex is the most important condition for their innovative development today. Most of these activities are based on the results of research and development work carried out with the aim of creating new diversified products. The effect of the implementation of these works is to change the range of products created, improve their quality, increase labor productivity, etc. The effectiveness of research and development activities aimed at ensuring the process of production diversification largely depends on the method of calculating their price. The article presents proposals for the development of procedures for evaluating research and development works and forecasting their prices in today's difficult economic conditions that have a negative impact on the process of production diversification.Scientific novelty: based on the analysis of the general laws of management theory, the system of criteria is analyzed and refined, which is used for evaluating research and development work performed by scientific organizations and design bureaus in the interests of implementing production diversification programs at enterprises of the military-industrial complex. Based on the formulated methodology, which takes into account the specifics of pricing for the results of research and development work carried out in the interests of ensuring national security, proposals have been elaborated for the development of techniques for economic evaluation of these works and tools and for predicting their prices.Practical significance: the results of the study can serve as a basis for the development and adjustment of plans for the implementation of scientific works carried out to provide for production diversification at the enterprises of the military- industrial complex.